Iterative learning and feedback control for the curvature and contact force of a metal strip on a roll. (April 2022) - Stadler, G.; Steinboeck, A.; Marko, L.; Deutschmann-Olek, A.; Kugi, A.
Abstract: This paper presents a novel model-based control strategy for the curvature and the contact force at the contact point of a metal strip and a roll. Due to the plastic deformation of the strip, the bending history of the strip has to be considered in the controller design. A multivariable two-degrees-of-freedom (2-DOF) control structure is used to track user-defined periodic references for the outputs. The proposed multi-input/multi-output (MIMO) feedback control structure consists of a spatial iterative learning control (ILC) combined with a multivariable PI controller. The control strategy is implemented in a real-time system and verified by measurements on an experimental test rig.